1983
DOI: 10.4315/0362-028x-46.4.276
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Yersinia enterocolitica in Raw and Pasteurized Milk

Abstract: Raw milk (100 samples) and pasteurized milk (100 samples) were assayed for presence of Yersinia enterocolitica, using four different enrichment and post-enrichment techniques. Isolation of Y. enterocolitica was made on MacConkey agar and Cefsulodin-Irgasan-Novobiocin (CIN) agar directly from incubated broths containing the milk, and after treatment of enrichment broths with a potassium hydroxide solution. Twelve samples of raw milk and one of pasteurized milk contained Y. enterocolitica. Nearly all isolates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 0 publications
1
12
0
1
Order By: Relevance
“…Epidemiological studies in food microbiology revealed that refrigerated food stored over a long period pose an additional risk, because Yersinia, as a psychrotrophic microbe, is able to grow at temperatures as low as 0°C (Hanna, Zink, Carpenter, & Vanderzant, 1976). These microorganisms have been isolated in different countries from raw milk: in Australia (Ibrahim & Mac Rae, 1991;Hughes, 1979), Canada (Schiemann, 1978), France (Vidon & Delmas, 1981), Ireland (Walker & Gilmour, 1986), Italy (Franzin, Fantino, & Vidotto, 1984) and USA (Moustafa, Ahmed, & Marth, 1983) but, the incidence of Y. enterocolitica in derived dairy products was rarely reported (Hamama, Marrakchi, & el Othmani, 1992;Schiemann, 1978). The first, food-associated outbreak of yersiniosis occurred in New York, where over 220 individuals were stricken with acute intestinal illness after consumption of contaminated milk (Black et al, 1978).…”
Section: Introductionmentioning
confidence: 96%
“…Epidemiological studies in food microbiology revealed that refrigerated food stored over a long period pose an additional risk, because Yersinia, as a psychrotrophic microbe, is able to grow at temperatures as low as 0°C (Hanna, Zink, Carpenter, & Vanderzant, 1976). These microorganisms have been isolated in different countries from raw milk: in Australia (Ibrahim & Mac Rae, 1991;Hughes, 1979), Canada (Schiemann, 1978), France (Vidon & Delmas, 1981), Ireland (Walker & Gilmour, 1986), Italy (Franzin, Fantino, & Vidotto, 1984) and USA (Moustafa, Ahmed, & Marth, 1983) but, the incidence of Y. enterocolitica in derived dairy products was rarely reported (Hamama, Marrakchi, & el Othmani, 1992;Schiemann, 1978). The first, food-associated outbreak of yersiniosis occurred in New York, where over 220 individuals were stricken with acute intestinal illness after consumption of contaminated milk (Black et al, 1978).…”
Section: Introductionmentioning
confidence: 96%
“…and Yersinia enterocolitica in farm bulk tank milk (BTM) (Lovett, Francis, & Hunt, 1987;McManus & Lanier, 1987;Moustafa, Ahmed, & Marth, 1983;O'Donnell, 1995;Rahn et al, 1997;Rohrbach, Draughon, Davidson, & Oliver, 1992;Steele et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Schiemann and Toma (1978) recovered Y. enterocolitica only from 1 of 165 samples of pasteurized dairy products produced in Ontario, Canada. Similarly, Moustafa et al (1983) recovered Y. enterocolitica from 1% of pasteurized milk samples examined, while Tibana et al (1987) recovered the pathogen from 13.7% of pasteurized milk samples produced in Rio de Janeiro, Brazil. Twenty-two of the 41 isolates were capable of producing heat-stable toxin in culture media but not in sterile whole milk.…”
Section: G Pathogensmentioning
confidence: 91%
“…High prevalence was also reported for goat milk (Jensen and Hughes, 1980;Walker and Gilmour, 1986). However, strains of Y. enterocolitica possessing virulent characteristics, or biotypes and serovars associated with human illness, are rarely isolated from raw milk (Moustafa et al, 1983;Jayarao and Henning, 2001), although non-virulent serotypes are.…”
Section: Pathogensmentioning
confidence: 96%
See 1 more Smart Citation